TOEIC Smart : Red book listening. (Nxb. Tổng hợp Tp.HCM : Nhân Trí Việt, 2012)
Lesson 1: Graphs & charts; Lesson 2: Instructions; Lesson 3: Letters & memos; Lesson 4: Notices & advertisements; Lesson 5: Articles; Lesson 6: Reading comprehension strategies; Lesson 7: Skimming; Lesson 8: Scanning; Achievement test and answer key.